Transcriptional Control of Photosynthesis Genes: The Evolutionarily Conserved Regulatory Mechanism in Plastid Genome Function - Puthiyaveetil, Sujith; Ibrahim, Iskander M.; Jeličić, Branka; Tomašić, Ana; Fulgosi, Hrvoje; Allen, John F. (Genome biology and evolution, 2010)
Chloroplast sensor kinase (CSK) is a bacterial-type sensor histidine kinase found in chloroplasts--photosynthetic plastids--in eukaryotic plants and algae. Using a yeast two-hybrid screen, we demonstrate recognition and interactions between: CSK, plastid transcription kinase (PTK), and a bacterial-type RNA polymerase sigma factor-1 (SIG-1). CSK interacts with itself, with SIG-1, and with PTK. PTK also interacts directly with SIG-1. PTK has previously been shown to catalyze phosphorylation of plastid-encoded RNA polymerase (PEP), suppressing plastid transcription nonspecifically. Phospho-PTK is inactive as a PEP kinase. Here, we propose that phospho-CSK acts as a PTK kinase, releasing PTK repression of chloroplast transcription, while CSK also acts as a SIG-1 kinase, blocking transcription specifically at the gene promoter of chloroplast photosystem I. Oxidation of the photosynthetic electron carrier plastoquinone triggers phosphorylation of CSK, inducing chloroplast photosystem II while suppressing photosystem I. CSK places photosystem gene transcription under the control of photosynthetic electron transport. This redox signaling pathway has its origin in cyanobacteria, photosynthetic prokaryotes from which chloroplasts evolved. The persistence of this mechanism in cytoplasmic organelles of photosynthetic eukaryotes is in precise agreement with the CoRR hypothesis for the function of organellar genomes: the plastid genome and its primary gene products are Co-located for Redox Regulation. Genes are retained in plastids primarily in order for their expression to be subject to this rapid and robust redox regulatory transcriptional control mechanism, whereas plastid genes also encode genetic system components, such as some ribosomal proteins and RNAs, that exist in order to support this primary, redox regulatory control of photosynthesis genes. Plastid genome function permits adaptation of the photosynthetic apparatus to changing environmental conditions of light quantity and quality.